NORMATIVE-LEGAL BASIS OF RECOGNIZING, ACCOUNTING AND REFLECTING INCOME AND COSTS IN MEDICAL INSTITUTIONS IN FINANCIAL STATEMENTS (Marketing Journal, 2025)
This article describes the regulatory framework for the recognition, accounting, and reflection of income and expenses in financial statements in medical institutions. In particular, the regulatory framework for accounting for income and expenses in medical institutions is described by classifying them into specific groups, and conclusions are drawn based on the research results.
Keywords: medical institution; state medical institution; income; expenditure; accounting; budget accounting; budget accounting standards; accounting policy